Relationship between edaphic macrofauna and soil chemical attributes in different agroecosystems - Lima, Sandra Santana; Aquino, Adriana Maria de; Leite, Luiz Fernando Carvalho; Velásquez, Elena; Lavelle, Patrick (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this study was to evaluate land use effects on the abundance and diversity of invertebrate macrofauna and its relationship with the soil chemical characteristics in different agroecosystems. Five systems were studied: ecological based system at three years of adoption (ES3), agroforestry systems at six (AFS6) and ten years of adoption (AFS10), slash and burn agriculture (SBA), and native forest (NF). In each system, five samples were collected in the form of soil monoliths (25x25 cm) at 10 cm depth, during the dry (October 2006) and rainy seasons (May 2007). The relationship between edaphic macrofauna and chemical attributes in the different land use systems was determined by coinertia analysis. The highest abundance of macrofauna was observed in the rainy season. Systems SE3, SAF6 and SAF10 showed higher species richness and indices of Shannon and Pielou, regardless of the sampling season. The agroforestry management favored the occurrence of "ecosystem engineers". Agroforestry systems provide better soil chemical characteristics and increase soil invertebrate macrofauna abundance and richness.